Rancangan Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 pada Materi Menulis Paragraf Beraksara Jawa dengan Model Pembelajaran Blended Learning di Mts N 1 Tegal - Widiyanti, Isnen (Cakrawala: Jurnal Pendidikan, 2022)
Education in Indonesia is currently required to prepare students who are smart, creative and independent. This is in line with the expectations of the achievement of 21st century skills. Where learning is not only centered on cognitive abilities, but also includes a number of personal and social skills. Known as the 4Cs of 21st Century Learning: critical thinking, creativity, collaboration, and communication. Advances in Information and Communication Technology provide tremendous benefits for the world of education. All can be easily done without any limits because each individual can do it himself. Such a broad impact has given a new color or face in the education system in this world. This is evidenced by the many developments of learning models that refer to information technology-based learning. This paper helps provide information to teachers about how to apply Blended Learning at MTs N 1 Tegal. For online learning, teachers use constructivist pedagogical strategies, this is chosen to make it easier for teachers to deliver learning which is considered very helpful because it includes interaction, collaboration, projects, problem-based. Our online learning process requires a cellphone and a data package to be able to convey and receive messages. Offline learning itself, the teacher conveys his learning using only 4 learning strategies which include guided discovery, discussion, demonstration and cooperative learning, this is done because of the limited time for offline learning.